DEVELOPMENT OF A HYBRID MODEL FOR THE EFFECTIVE DISTRIBUTION OF WATER RESOURCES BASED ON A PREDICTION MODEL - Ospan Ә.Ғ; Mansurova М.Е; Kakimzhanov Е.Х (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The development of a model for the effective use of water resources is one of the priorities of Kazakhstan. About half of the Republic’s surface water (44.9 cubic km) comes from the territory of neighboring countries. According to experts, the increasing water intake by neighboring countries and the deterioration of water quality in the country’s rivers can lead to an environmental disaster. In this regard, the analysis and discussion of models for the efficient allocation of water resources in transboundary river basins, which are already successfully used in the world, will be an urgent solution. This article discusses effective models and ways to solve water resources problems in transboundary rivers that have already been applied to transboundary rivers, and based on these models, a hybrid model is built that can be applied to transboundary rivers of the country.